Phonological Orchestration and Structural Unity: The Dual Role of the Fawasil - Abalkheel, Albatool; Sourani, Maha; ElZohbi, Sawsan (Forum for Linguistic Studies, 2025)
Given the profound impact of “Fawasil” on an individual’s psyche and receptiveness to conveyed concepts and meanings, this descriptive-analytical study examines how “Fawasil” enhances engagement with Qur’anic messages, highlighting their phonetic elegance and semantic depth. The analysis focuses on auditory phenomena such as addition, deletion, taskeen, elongation, and ghunnah, examining verses from Surah(s): Al-Ahzab, Al-Haqqah, AS-Shuaraa, Yusuf, HUD, SAD, NUH, Ad-Dariyat, and Al-Baqara, in chapters 33, 69, 26, 12, 11, 38, 71, 19, 51, and 2, respectively. They are selected for their thematic richness, dialogic complexity, and structural diversity, highlighting their role in maintaining cohesion and coherence. This study employs Jakobson’s Phonological Features of Aesthetic Communication, which could be relevant for exploring the interplay of sound and meaning. English translations and phonetic transliterations accompany the analysis, offering insights into the Qur’an’s linguistic subtleties and sophisticated methods of effectively conveying divine messages. The findings highlight that the Fasila enhances the acoustic dimension of expression. Additionally, deletions in the Fawasil stem from a deliberate focus on phonetic harmony and semantic coherence. The study also reveals that taskeen preserves phonetic consistency despite grammatical variations across verses. Furthermore, the sound /nun/ contributes to the precision of the Fawasil. Another key observation underscores the intricate prosodic patterns within the text, where repetition and parallelism play a crucial role in deepening the understanding of Qur’anic phonetics. Finally, the study offers recommendations to guide future research in this area.